INFORMATION AND COMMUNICATION TECHNOLOGIES AS A MANAGEMENT INSTRUMENT FOR UKRAINE’S INFRASTRUCTURE RECONSTRUCTION PROCESSES IN THE CONTEXT OF EUROPEAN INTEGRATION - Бражко, Олена (SWorldJournal, 2026)
This article examines the role of information and communication technologies (ICTs) as a governance instrument for the post-war reconstruction and modernization of Ukraine’s critical infrastructure within the context of European integration. It substantia